The relationships among nature connectedness, climate anxiety, climate action, climate knowledge, and mental health - Thomson, Emily E.; Roach, Sean P. (Frontiers in Psychology, 2023)
Climate change is a source of global concern that has both direct and general impacts on mental health. A recent study conducted following severe bushfires in Australia demonstrated relationships among nature connectedness, climate action, climate worry, and mental health; for example, nature connectedness was associated with climate worry, which in turn was associated with psychological distress. The present study sought to replicate those findings while building on them in two important ways: on those findings in two ways: first, test similar relationships in a different geographical context that has been mostly spared from direct impacts by acute climate events; second, we take into consideration an additional factor, climate knowledge, which has been linked to relevant factors such as climate anxiety.. The results of a survey completed by 327 adults revealed a similar relationship between nature connectedness and climate anxiety, and between that and psychological distress. Further mirroring those previous findings, nature connectedness was associated with both individual and collective climate action, but the relationships between them and psychological distress differed. The proposed model was a better fit to the collected data among those with high levels of climate change knowledge than those with low levels, suggesting that such knowledge influences how the above factors relate to each other.